Sufi Orders, Zakat-Infaq-Sadaqah (ZIS), and the Muslim Community’s Economy: A Study on the Integration of Spirituality and Social Justice - Budi Rahman Hakim; Rizaluddin Kurniawan; Fajrur Rahman (International Journal of Zakat, 2026)
Purpose This study aims to critically examine the integration of Sufi spirituality, zakat-infaq-sadaqah (ZIS) philanthropic governance, and sustainable community economic development through the contemporary neo-Sufi approaches of prominent ṭarīqahs (Sufi orders) in Indonesia. Design/Methodology/Approach Focusing on TQN Suryalaya, Tariqa Idrisiyyah, and Tariqa Shiddiqiyyah, the research employs a qualitative-critical method that combines content analysis with a Foucauldian genealogical approach to analyze primary institutional texts and internal records. Findings The findings reveal that these groups successfully transmogrify core religious values—such as ikhlāṣ (sincerity), amānah (trustworthiness), and adab (moral conduct)—into a participatory, social-justice-oriented framework for economic governance. Rather than dispensing mere consumptive charity, ZIS functions as a transformative empowerment and social rehabilitation tool via pesantren cooperatives and Sufi-influenced entrepreneurship (sufipreneurship). However, the study identifies critical challenges threatening this system, including the commercialization of religious values, symbolic reduction of Sufism, and bureaucratic secularization of ZIS management. Research limitations/implications Acknowledging qualitative and geographic limitations, future research should pursue quantitative regional impact assessments and cross-national comparative studies. Practical implications Consequently, practitioners and state regulators must integrate qualitative spiritual values (tazkiyah) into their standard operating procedures, protecting Islamic philanthropy from sheer administrative compliance. Social implications By transforming passive charity recipients (mustahik) into active, ethically driven economic agents, this model offers a robust communal mechanism to eradicate structural poverty, foster intercommunity solidarity, and build grassroots socio-economic resilience. Originality/value Ultimately, this study pioneers the "Dzikir Economy"—a highly novel transcendental framework synthesizing classical Sufi moral depth with modern organizational efficiency, offering an ethical alternative to conventional, legal-formal Islamic finance. Keywords: Neosufism; Zakat; Islamic Spirituality; Community Economy; Social Justice.